Meningkatkan Hasil Belajar Siswa Dalam Materi Simbol Sila Pancasila Pada Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan (PPKN) Dengan Menggunakan Media Puzzle Pada Siswa Kelas III Di SDN Cilaja 2 Pandeglang - Siti Sofia Nurwahyuni; Rifki Arif Nugraha; Ratna Dewi; Ajeng Mulia Sari (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
Based on initial observations in class III SDN Cilaja 2 Pandeglang, it was found that student problemswere in the way of teaching the teacher who tended to be monotonous and rarely used learning media.Besides that, sometimes the teacher only gave assignments in the form of orders so that students copied thematerial in the textbooks, while some of the students had not master reading and writing skills. This causeslow learning outcomes for students, especially in Civics subjects which are still below the KKM. Toovercome this, it is necessary to apply learning innovations using learning media, one of which is usingPuzzel media with the formulation of the problem "How to use Puzzle Media on Material Symbol of thePancasila Precepts in Pancasila and Citizenship Education Subjects (PPKn) in class III SDN Cilaja 2Pandeglang? And how can the learning outcomes of Pancasila and Citizenship Education (PPKn) on thePancasila precepts symbol material using puzzle media improve student learning outcomes in class III atSDN Cilaja 2 Pandeglang?"This type of research is Classroom Action Research (PTK) which consists of III cycles. In carrying out thistype of PTK research, it only involved one class as an experimental class without any comparison classwhich aimed to determine the effectiveness of Civics learning using Puzzle media in class III students atSDN Cilaja 2 Pandeglang. The data in the study were collected using observation techniques, tests,interviews and documentation.The results of the research carried out showed an increase, namely in the pre-cycle the average studentcompleteness was 50.94 with a completeness percentage of 32%. in the first cycle it was 41% with anaverage value of 55.32, in the second cycle it was 68% with an average value of 62.76 and in the thirdcycle it was 88% with an average value of 80.23. With these results, it can be concluded that studentlearning outcomes through the use of puzzle media can increase as desired from the research results andpuzzle media are expected to be used in Civics lessons to improve student learning outcomes